Low-level laser therapy: A noninvasive method of relieving postactivation orthodontic pain-A randomized controlled clinical trial - Subramaniam Murugesan Vignesh Prasad; Turuvekere Ramaiah Prasanna; Vijayarangan Kumaran; Nagaraj Venkatachalam; Mohamed Ramees; Esther A Abraham (Wolters Kluwer Medknow Publications, 2019)
Introduction: Pain is an unavoidable squeal of orthodontic treatment and it is known to decrease patient compliance and eventually affects treatment results. Numerous methods are available in literature to manage orthodontic pain after activation but they have their own limitations. This has led to exploring further options for management of pain. Aim: The aim of this study was to evaluate the effectiveness of low-level laser therapy (LLLT) in alleviating orthodontic pain after activation. Materials and Methods: 20 subjects were randomly divided into an experimental and a control group. Each participant was given a retraction force of 200gm/cm2/side. Subjects in the experimental group were exposed to low-level laser light at 980nm and those in the control group were exposed to red LED light as placebo. The pain perceived after 0 hour, 1 hour, 3 hours, 48 hours, and 1 week of activation was recorded by patient using Visual Analog Scale. Statistical analysis was done using Mann-Whitney test. Results: Results of the study showed that pain experienced by the subjects after orthodontic activation was higher in experimental group at T0 than in placebo group. At T1, T2, T4, and T5, the pain experienced by the subjects was less in the experimental group compared to the placebo group. Pain experienced by the subjects in the experimental group at T3 was significantly less as compared to those in the placebo group. Conclusion: A single dose of LLLT at 980nm, 2.5 W/cm2, and 600 J is effective in relieving orthodontic pain after activation.